(untitled) (Scientific journal of the Fergana State University, 2023)
The article focuses on the role of Zahiriddin Muhammad Babur’s views on the philosophy of love in improving the moral and aesthetic thinking of young people. Also in his spiritual heritage, in works of moral and aesthetic content, such leading principles as moral beauty and moral unity, love and hatred, free will and destiny, good intentions were singled out.